Efeito protetor do laser de baixa potência em diferentes momentos sobre o processo de reparo do músculo esquelético de ratos - Ribeiro, Beatriz Guimarães (2017)
The low level laser therapy (LLLT) is a resource capable of modulating in a positive way the different stages of the muscle repair process. However, little has been described about its effects when applied prior to injury, associated or not with post-injury treatment. The general objective of the present study was to evaluate the effect of LLLT applied prior to the muscle injury associated or not to the post-injury application on the rat skeletal muscle repair process. The aim of article 1 was to evaluate the effect of infrared LLLT applied prior to cryoinjury on the expression of IL-6, MyoD and myogenin. The aim of article 2 was to evaluate the effect of red and infrared LLLT prior to cryoinjury associated or not with post-injury application on oxidative stress. The aim of article 3 was to evaluate the effect of infrared LLLT applied prior to injury with or without post-injury application on the gene expression and protein synthesis of inflammatory cytokines TNF-α and IL-6, and muscle morphology. For the three studies, 205 Wistar rats were divided into the following experimental groups: Control; Injury; LLLT 660 nm prior to injury; LLLT 780 nm prior to injury; LLLT 660 nm pre- and post-injury; and LLLT 780 nm pre- and post-injury. The cryoinjury consisted of two applications of cane cooled in liquid nitrogen in the anterior tibial muscle (TA). The injured groups were evaluated at 1, 3, 7 and 14 days after injury (only for oxidative stress analysis, evaluation occurred at 1, 3, and 7 days). LLLT irradiation was performed with the AsGaAl laser (780 nm) at the parameters of 10 J/cm²; 40 mW; 10 seconds per point; 8 points; 3.2 J. At the end of the protocol, TA muscles were carefully removed for analysis of oxidative stress by lipid peroxidation (LPO) by chemiluminescence initiated by t-BOOH, protein oxidation through the carbonyl damage assay, and analysis of antioxidant enzymes: catalase (CAT), superoxide dismutase (SOD) and glutathione peroxidase (GPx). TNF-α and IL-6 cytokines were analyzed by quantitative real-time PCR for the detection of gene expression. In addition, a morphological analysis was performed by staining with hematoxylin and eosin. TNF-α and IL-6 cytokines were analyzed by ELISA for protein expression. Data were expressed as mean and standard error of the mean because they were parametric and the comparison between the groups was performed by ANOVA/Tukey (p<0.05). The results of article 1 demonstrate a reduction in the levels of IL-6 mRNA in the group irradiated prior to the injury, concluding that the LBP applied prior to injury was able to modulate positively this inflammatory cytokine, but had no effect on the myogenic regulatory factors MyoD and myogenin in the evaluated parameters. The results of article 2 containing the oxidative stress analysis showed that the irradiated groups presented reduction of the lipoperoxidation and positive modulation of the antioxidant enzymes during the muscle repair process, concluding the red and infrared laser were able to modulate positively the oxidative stress, being the most effective infrared laser in the modulation of antioxidant enzymes. The results of article 3 demonstrated a reduction in the gene expression of TNF-α in the group irradiated prior to injury. In the pre-and post-injury irradiated group, IL-6 and TNF-α mRNA levels increased during the skeletal muscle repair process, concluding that the infrared laser was able to positive modulation these inflammatory cytokines in the two forms of application. Therefore, it is concluded that the LLLT irradiated prior to injury associated or not with the post-injury application has a beneficial effect on inflammatory cytokines and oxidative stress during the repair of the skeletal muscle of rats.